Peak-at-Intermediate-Salinity Transcriptional and Histological Responses of Triploid Rainbow Trout Gills to Salinity Gradients - Yanming Sui; Jingtao Liu; Haopeng Hu; Yan Ji; Yuanhao Ren; Bo Qin; Na Ying; Tingting Lin; Siping Li; Hanfeng Zheng; Lei Li (Fishes, 2026)
Using a three-factor orthogonal design, we investigated the transcriptomic and histological responses of triploid rainbow trout (Oncorhynchus mykiss) gills across three salinities (10, 20, and 30 ppt) over 60 days, with temperature and body size as background conditions. Results showed that 20 ppt was associated with extensive transcriptional reprogramming, with 3333 differentially expressed transcripts (DETs), whereas 30 ppt induced only 120 DETs; WGCNA further identified salinity-correlated modules involved in ion transport and ribosome biogenesis. Histological alterations remained within physiological ranges with no salinity-dependent severity gradient, as confirmed by semi-quantitative scoring. These findings demonstrate that triploid rainbow trout gills employ distinct molecular strategies at medium versus high salinity. Within the 10–30 ppt range examined, 20 ppt was the salinity at which transcriptional reprogramming was most active, suggesting that this intermediate salinity warrants further investigation as a potential acclimation stage.

Clay minerals reduced antibiotic resistance gene dissemination in the plant rhizosphere through inhibiting horizontal gene transfer and reshaping microbial community structure - Yuxin Qin; Yuqiu Luo; Haihui Fu; Haopeng Pang; Xiaoyu Long; Qian Zhang; Hai Lin; Bing Li (Journal of Environmental Chemical Engineering, 2026)

Whole Gracilaria biomass as a green emulsifier for pickering emulsions: Applications in astaxanthin delivery and fat replacement - Xiaoyang Shao; Lin Chen; Haopeng Su; Xiumin Zhang; Haitao Wang; Dayong Zhou; A.M. Abd El-Aty; Mingqian Tan (Food Hydrocolloids, 2026)

An improved ISPH model for simulating wave–current interactions and turbulence evolution over submerged reefs - Dong Wang; Haopeng Wang; Sheng Yan; Jianguo Lin; Jiawen Sun; Jingdan Cui; Junyi Xi; Tao Liu (Ocean Engineering, 2026)

Construction of Pickering emulsion stabilized by whole components from Spirulina for astaxanthin delivery and 3D printing - Haopeng Su; Feng Wang; Xiaoyang Shao; Lin Chen; Lei Lin; Taixu Wu; Yemeng Shen; Shuang Cong; Mingqian Tan (Food Bioscience, 2026)

Regulating electrode wettability by construction of the liquid-liquid interface for improving metal electrodeposition performance - Chenrui Lan; Haopeng Feng; Lingyue Zhang; Jiawei Yue; Yangfeng Wu; Jiajia Wang; Jing Tang; Lin Tang (Chemical Engineering Journal, 2026)

Obstacles and bottleneck breakthroughs affecting the development of hydroxyl radicals assisted chemical mechanical polishing - Xingwang Xu; Bin Lin; Haopeng Chen; Bingrui Lv; Jinming Li; Pengcheng Zhao; Jingguo Zhou; Junqing Jia; Tianyi Sui; Jieqiong Lin (Journal of Environmental Chemical Engineering, 2025)

Selective recovery of precious metals from E-waste leachates using zinc-modified biochar in capacitive deionization - Yangfeng Wu; Haopeng Feng; Tang Jing; Chenrui Lan; Nile Wu; Nana Chai; Jiawei Yue; Lin Tang (Desalination, 2025)

Insight into the mechanism of pyrolysis temperature on the performance of biochar-based MOF materials in capacitive deionization for heavy metal removal - Yangfeng Wu; Haopeng Feng; Jing Tang; Chenrui Lan; Nile Wu; Nana Chai; Jiawei Yue; Lin Tang (Desalination, 2025)

Structurally diverse alkaloids from the Buxus sinica and their cytotoxicity - Liwu Lin; Jiaxin Xu; Lu Chai; Haopeng Dai; Xingrong Peng; Minghua Qiu (Phytochemistry, 2024)

Research progress on remediation of heavy metal contaminated soil by electrokinetic-permeable reactive barrier - Zhenhao Yang; Jing Tang; Haopeng Feng; Xi Liu; Xiaojie Zhuang; Hongbin Wang; Yangfeng Wu; Yuyao Guo; Lin Tang (Chemical Engineering Journal, 2024)

An integrated calibration strategy for the development and validation of an LC-MS/MS method for accurate quantification of egg allergens (Gal d 1–6) in foods - Shupeng Yang; Jingjing Chen; Mohamed F. Abdallah; Haopeng Lin; Peijie Yang; Jianxun Li; Rong Zhang; Qianqian Li; Peng Lu; Shuyan Liu; Yi Li (Food Chemistry, 2024)

A versatile CuCo@PDA nanozyme-based aptamer-mediated lateral flow assay for highly sensitive, on-site and dual-readout detection of Aflatoxin B1 - Xu Zhu; Jing Tang; Xilian Ouyang; Yibo Liao; Haopeng Feng; Jiangfang Yu; Li Chen; Yating Lu; Yuyang Yi; Lin Tang (Journal of Hazardous Materials, 2024)

Short-term ambient particulate matter pollution of different sizes and respiratory hospital admission in the Beibu Gulf area of Southern China - Haopeng Li; Lizhong Liang; Shiyu Zhang; Zhengmin (Min) Qian; Miao Cai; Xiaojie Wang; Stephen Edward McMillin; Amy E. Keith; Jing Wei; Yan Geng; Hualiang Lin (Atmospheric Environment, 2023)

Ambient air pollution, bone mineral density and osteoporosis: Results from a national population-based cohort study - Yin Yang; Rui Li; Miao Cai; Xiaojie Wang; Haopeng Li; Yinglin Wu; Lan Chen; Hongtao Zou; Zilong Zhang; Haitao Li; Hualiang Lin (Chemosphere, 2023)

Spatial-Temporal Change of Phytoplankton Biomass in the East China Sea with MODIS Data - Yumei Wu; Haopeng Zhu; Xiaoyan Dang; Tianfei Cheng; Shenglong Yang; Lin Wang; Liangmin Huang; Xuesen Cui (Journal of Ocean University of China, 2021)